Assessing the urban and rural stage bus services disparities in peninsula Malaysia - Ponrahono, Zakiah; Bachok, Syahriah; Mohamed Osman, Mariana; Ibrahim, Mansor; Abdullah, Muhammad Faris; Abdullah, Alias (Malaysian Institute of Planners, 2015)
Disparities between services and goods provision have been the concerns of various regional development proponents. Among the gaps that needed to be addressed by regional policies and initiatives were accessibility and mobility levels between urbanites and the rural population. This study reports on the differences of the urban versus rural bus services. For this purpose, this study extends the exploration of approximately 48 routes within selected urban and regional settlements in Peninsula Malaysia, using a quantitative traffic engineering measure known as Level of Service standards or LOS. Three performance measures, namely fixed-route hour of service, fixed-route service frequency and passenger-load threshold were evaluated in determining the existence and extent of such disparities. The passengers’ satisfaction and preference survey were conducted to complement some qualitative explanations left void by the LOS evaluation. Methods of on-board face to face intercept survey and adoption of Geographical Information System (GIS) /Global Positioning System (GPS) were deployed in the collection of primary data. More than 1600 survey forms were distributed, but after collection and data cleaning, only a total of 1130 were analysed. Findings of the study supported and confirmed the existence of such spatial imbalances of services provision. They also further accentuated that many developing nations’ rural settlements were indeed stigmatised by a lower level of stage bus services (average at LOS D) compared to those enjoyed by the urbanites (average services at LOS C).